The role of inter-organizational networks in enabling or delaying disruptive innovation: a case study of mVoIP. Issue 6 (4th July 2016) - Hynes, Niki; Elwell, Andrew David
Abstract : Purpose: The Purpose of this paper is to investigate the role of inter-organizational networks in the emergence of a disruptive technology by taking a snapshot view of the UK market for mobile VoIP technologies. By delineating the technologies required for an mVoIP call to occur, the role of incumbents, technology, and inter-organizational networks is explored. Design/methodology/approach: The paper uses a case study approach using secondary data from a variety of sources including company websites, newspapers, technical press and users to form a picture of the current situation. Findings: We show that inter-organizational networks can act both to enable and delay disruptive technologies. We discuss the difference between collaborative and collective actions and the way in which these can slow or even prevent a new technology emerging Research limitations/implications: The paper is based on secondary data and the research results may lack generalizability to other technologies Practical implications: The need for new business models for mobile VOIP is discussed. Originality/value: Disruptive technologies are difficult to predict or map until after the market disruption has occurred. This paper aims to map a disruptive technology at a point in time when the technology is still emerging. The study is based on a comprehensive analysis of technology and market actions and based on secondary data: it is limited at the detailed level to one geographic market but provides a unique snapshot of an emerging disruptive technology.